"Apanhando desperdícios" ou "Contra o desperdício da experiência": cartografia de coletivos em busca de educação emancipatória no município de Sorocaba - José, Caio Rennó (2016)
Our studies are characterized by the analysis of the production of resigned/reified/individualistic subjectivity as a product deliberated by the capitalist power dynamics that, by the control's reinventions, decrease life and dehumanize relationships between people and people with nature. The discussions that have been realized highlight the subjectivity, social life organization and educational processes which curb the production of singular/rebel subjectivities. However, we understand at the same time the control mechanisms deepen, the resistances have also reinvented themselves. We highlight disruptive aspects among a power dynamics that captures the creation potential in our daily routine and in the common's production. We have found horizontal organizations, themes, informals and collectives that have been acting micropolitically and opening gaps in a scenario that is reverse to life's expantion. This investigation's snippet has been done as a cartography of the collectives that are searching for an emancipatory education in Sorocaba-SP, Brazil, willing to comprehend their dynamics and organization modes, besides their educative aspects, that produce rebel subjectivities inherent to the experience with the collective actions participation.